Scientific literacy profile in biological science of high school students - Novaristiana R; Yudi Rinanto; Murni Ramli (University of Muhammadiyah Malang, 2019)
Scientific literacy is very important for students, so that they can live in the 21st-Century, including solving problems that occur in everyday life. This study was aimed to get an overview of the high school students’ scientific literacy profile in biology learning in the Surakarta City, Central Java, Indonesia. This research was ex-post-facto, looking at the effects of school type and school status. The population was 8750 students from General High Schools, Vocational High Schools, and Islamic High Schools. The sample of 334 students was selected using the proportionate stratified random sampling. The data were collected using scientific literacy tests. The test instrument was prepared by translating the PISA tests on biology from 2006 to 2015 into Indonesian. The test does not take place simultaneously in all schools. The results showed the high school students’ biological science literacy in Surakarta City was very low, except for the private IHSs students, who gained the low category. If viewed from the trend of the achievement levels, high school students in Surakarta City get the lowest achievement level at level 6 and highest at level 5. It concluded the high school students’ scientific literacy in Surakarta City were very low.